The oxidative activation of Ca²⁺/calmodulin-dependent protein kinase II: a double-edged sword for health and disease - Wang, Qinchuan (2022)
The Calcium/Calmodulin-dependent protein kinase II (CaMKII) is a versatile signaling protein involved in many cellular processes. It is considered a promising therapeutic target for cardiovascular disease. CaMKII is uniquely capable of integrating various upstream signaling inputs, including redox signals, to regulate a wide range of downstream targets. The activation of CaMKII through the oxidation of a pair of oxidant-sensitive residues in its autoinhibitory region has been established as a significant driver of diseases. However, recent findings suggest that this oxidative activation mechanism is highly conserved and plays critical physiological roles. CaMKII oxidation, thus, is an example of evolutionary trade-offs that confer fitness benefits but also increase disease susceptibility. Understanding how CaMKII oxidation is regulated, and what downstream targets are regulated by oxidized CaMKII will help enhance the benefits while minimizing the detriments of this double-edged sword.